Kegiatan Analisis Keabsahan Soal Ujian Seni Budaya (Tari) Oleh Guru Di SMP Negeri 3 Koto XI Tarusan Kabupaten Pesisir Selatan - Widia Mayang Sapitri; Yos Sudarman (SENDRATASIK UNP, 2019)
This article aims to describe the dance activity of the teachers at SMP Negeri 3 Koto XI Tarusan / Kabupaten Pesisir selatan in conducting the analysis of validity of the exam questions, especially that are used in the final exam. The criteria for validating the analysis of these questions have the same purpose as the measured and clear questions. The method used in this study was qualitative with descriptive analysis approach. The object of the research was the activity of the teacher in analyzing the questions of cultural art made by the teachers of SMP Negeri 3 Koto XI Tarusan, which amounts to 20 items. Those items have been tested to 20 students in the final examination of odd semester 2018/2019. The research instruments used were observation note, interview question lists and documentation files. In order to support the data collection activities, there were some steps such as doing observation, interview and documentation studies. The result of the research can explain that the questions of cultural arts analyzed by its validity has provided an overview of the improvement of the quality of education evaluation in school. The level of student learning outcomes, solely not caused by the level of students' ability in learning, it is also influenced by assessment instruments that are made like a question, whether it is valid or not. The result of the validity analysis of the cultural arts questions in the final exam at class VII-1 of SMP Negeri 3 Koto XI Tarusan were categorized as moderate difficult and 70% of the items have high validity.